Logical and semantic reconstuction of the story «The Switchman»: the dichotomy of «Truth and False» by Juan Jose Arreola (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
This paper investigates the literary text by means of logical and semantic analysis. Due to the method of component analyzing lexical unit semantics, the key definitions (concepts), which make up the text plot, are distinguished. Vocabulary schematization provides the use of method of classical and intuitionistic logics such as the principle of explosion, subsequently reconstructed in the truth table. All of the above-mentioned elements of logical-semantic analysis reproduce a clear connection between the structure and content of the text, as well as the connection between its empirical and substantive meaning.
Keywords: logical and semantic analysis; truth; false; structure; method of component analyzing lexical unit semantics; principle of explosion